Induction of syncytia by Moloney murine leukemia virus in myoblasts defective in differentiation. - Wong, P K (1977)
fu-1 cells, a nonfusing variant of the L8 line of rat myoblasts, form syncytia upon infection with murine leukemia virus (MuLV) or upon cocultivation with MuLV-infected cells; L8 cells do not form these syncytia, but do fuse into multinucleate myotubes. Syncytia of fu-1 cells form within 1 h after infection. The number of syncytia formed is proportional to the multiplicity of virus within a range of 4 to 16 and is maximum when the cell density is subconfluent. When either XC or fu-1 cells are productively infected with MuLV, they become resistant to syncytia formation by passage 3. The rapid formation of syncytia in fu-1 cells was found amenable for selection of temperature-sensitive mutants of MuLV and for screening additional variants of the L8 line.